2017
DOI: 10.21873/cgp.20015
|View full text |Cite
|
Sign up to set email alerts
|

The Multiple Roles of Exosomes in Metastasis

Abstract: Abstract. Exosomes are important contributors to cellMetastases are responsible for the death of a large majority of cancer patients despite considerable progress in surgical techniques, radiotherapy, chemotherapy and targeted therapies including immuno-therapy (1). A dramatic reduction of metastatic burden has been observed, however, tumor elimination is almost always incomplete. This phenomenon is based on drug resistance, which is due to adaptation of intracellular pathways or on activation of survival-supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
133
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(141 citation statements)
references
References 137 publications
2
133
0
3
Order By: Relevance
“…We next asked how macrophage cytoplasm is delivered to tumor cells. There are at least two mechanisms of cytoplasmic transfer – transfer of molecules extracellularly via secretion of extracellular vesicles (EVs), and transfer of molecules through cell-to-cell contact (Lou et al, 2017; McCoy-Simandle et al, 2016; Weidle et al, 2017)). The migration-promoting cytoplasmic transfer between tumor cells described by Zomer et al was via systemic transfer of EVs, however given the close and sustained physical interactions between macrophages and tumor cells observed in our zebrafish studies, we hypothesized that the cytoplasmic transfer from macrophages to tumor cells is cell-contact mediated.…”
Section: Resultsmentioning
confidence: 99%
“…We next asked how macrophage cytoplasm is delivered to tumor cells. There are at least two mechanisms of cytoplasmic transfer – transfer of molecules extracellularly via secretion of extracellular vesicles (EVs), and transfer of molecules through cell-to-cell contact (Lou et al, 2017; McCoy-Simandle et al, 2016; Weidle et al, 2017)). The migration-promoting cytoplasmic transfer between tumor cells described by Zomer et al was via systemic transfer of EVs, however given the close and sustained physical interactions between macrophages and tumor cells observed in our zebrafish studies, we hypothesized that the cytoplasmic transfer from macrophages to tumor cells is cell-contact mediated.…”
Section: Resultsmentioning
confidence: 99%
“…Li, Zhang, Zheng, Liu, & Chen, 2017; Pietrowska et al, 2017; Pocsfalvi et al, 2016; Sandfeld-Paulsen, Aggerholm-Pedersen, et al, 2016; Sandfeld-Paulsen, Jakobsen, et al, 2016; Sinha et al, 2018; Tanase et al, 2017; Taylor, Zacharias, & Gercel-Taylor, 2011; van Niel et al, 2018; Weidle et al, 2017)) (Fig. 1).…”
Section: Why Ceramide In Exosomes? It’s All In the Numbersmentioning
confidence: 99%
“…In cancer, exosomes reprogram tissue to allow growth of metastases, act as decoys to escape the immune system, or spread factors conferring resistance to drugs used in chemotherapy (Chiarugi & Cirri, 2016; Desrochers et al, 2016; Dorsam, Reiners, & von Strandmann, 2018; Dreyer & Baur, 2016; Kahlert & Kalluri, 2013; Kalluri, 2016; Ruivo, Adem, Silva, & Melo, 2017; S, Mager, Breakefield, & Wood, 2013; M. Silva & Melo, 2015; Steinbichler, Dudas, Riechelmann, & Skvortsova, 2017; Weidle, Birzele, Kollmorgen, & Ruger, 2017; H. G. Zhang & Grizzle, 2014; Zhao et al, 2017).…”
Section: Got Exosomes: What’s (Really) In Your Prep?mentioning
confidence: 99%
“…What is more, these vesicles can travel to distant sites of the organism and release the packed biomolecules into local and remote cells. Exosomes can bear different proteins including transmembrane proteins, such as major histocompatibility complex (MHC), and other intraluminal proteins and oncoproteins such as mutant KRAS[47]. Proteins delivered by exosomes can activate or inhibit different signalling pathways, altering cell function.…”
Section: Where Do Circulating Nucleic Acids Comes From and How Do Thementioning
confidence: 99%
“…As an example, it was demonstrated that exosomes increased cellular proliferation in gastric cancer cell lines by activating Akt phosphorylation[48]. Moreover, it has been described that TD exosomes can also facilitate cancer invasion and metastasis by regulating stromal cells, remodelling the extracellular matrix and stimulating angiogenesis[47,49]. …”
Section: Where Do Circulating Nucleic Acids Comes From and How Do Thementioning
confidence: 99%